PENGARUH STRATEGI PEMBELAJARAN KONTEKSTUAL DAN KONSEP DIRI TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Hellinawati, Hellinawati; Muhammad, Damris; Kamid, Kamid (Program Magister Teknologi Pendidikan Universitas Jambi, 2015)
The purpose of this study is to prove the existence of the learning effect of Contextual Teaching and Learning (CTL) strategy and the Self-Concept Toward Understanding Math Concepts Grade VIII MTs of Bangko. This research is the quantitative research, that’s the quasi-experimental. Data collection instruments such as questionnaires and tests the concept of self-understanding mathematical concepts. The research result are: (1) There is the influence of contextual teaching and learning strategies for understanding mathematical concepts. (2) There is the influence of self-concept to the understanding of mathematical concepts. (3) There were no effects of contextual teaching and learning strategies for understanding mathematical concepts to students who have a high self- concept. (4) There were no effects of contextual teaching and learning strategies for understanding mathematical concepts to students who have a low self-concept. (5) There is no interaction between learning strategy and self-concept. In this study it was found that CTL and self-concept in learning influence students' understanding of mathematical concepts, but CTL has a powerful role in increasing the understanding of mathematical concepts, regardless of whether the student is a high or low self-concept. Keyword: Contextual Teaching and Learning (CTL) Strategy, Self-Concept, and Understanding of Mathematical Concepts.